Developing Habitat Conservation Suitable For Nam Xouang Reservoir, Vientiane Province, Lao PDR - Dina Muthmainnah; Aroef Hukmanan Rais; Dondavanh Sibouthong (Program Pascasarjana Universitas Sriwijaya, 2019)
The establishment of the conservation area considers the most important issues of the environment changing in inland waters of ASEAN Countries. To respond this issue, a study was conducted in Nam Xouang Reservoir, Lao PDR, in 2018. To determine the conservation area, data and information were collected by mapping the deep waters area of spawning grounds, feeding ground, fishing seasons, and fish species caught. The data was collected with the support of six enumerators in upper-side and downside of the reservoir to identify the fish species and fish length-weight data. Results showed that built the display boards and warning signs is an effective way of considering simultaneously, to inform the local villagers about the fishing regulations and fish conservation zones. The participation of local fishing communities and local authorities might be necessary for the successful and sustainable management of the fisheries in the Nam Xouang Reservoir.